Left – Right Hand Coordination Using VTS.Sport And Underarm Floater Serve Accuracy Of Forth Year Female College Students - Naji, Jinan; Kailan, Badaa; Ali, Ishraq (Journal of Physical Education, 2018)
Left – Right Hand Coordination Using VTS.Sport And Underarm Floater Serve Accuracy Of Forth Year Female College Students The importance of the research lies in the effect of VTS. Sport on coordination and volleyball serve in forth year female college students 2015 – 2016. The problem of the research lies in not using modern updated means for testing and measuring like this system. The research aimed at identifying the relationship between left – right hand coordination using VTS. Sport and the accuracy of volleyball serving. The researcher used the descriptive method. The subjects were forth year female college students. The data was collected using proper statistical methods. The researcher concluded that there are significant differences between coordination tests and serving tests of forth year college students 2015 - 2016. In addition to that, they concluded that there is a correlation relationship between coordination test and serving tests for forth year college students 2015 – 2016. Finally the researchers recommended using cognitive tests using TMT-L and WAFR in other researchers and studies about sport psychology.